Korelasi intensitas bermain game online mobile legend dengan keterampilan sosial siswa MAN 3 Banda Aceh - Erizka Hasibuan; Martunis Yahya; Abu Bakar (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2019)
The intensity of playing mobile legend online games is how often a person uses his time to play mobile legend online games.Whereas social skills are the ability of individuals to be oriented towards achieving goals, values and acceptance in their social environment. This study aims to determine the relationship between the intensity of playing Mobile Legend games with students' social skills. This research was conducted with a quantitative descriptive approach and used observation scale techniques. The subject of this study was selected using purposive sampling, namely sampling based on certain characteristics or characteristics. Thesubjects of this study were MAN 3 students in Banda Aceh City who played the mobile legend game. The results showed that the intensity of playing mobile legend online games  for MAN 3 students in Banda Aceh City was in the category, while the quality of students' social skills was also in the medium category. The data analysis technique used in this study to answer the formulation of problems 1 and 2 is descriptive analysis of percentages, while the formulation of problem number 3 uses thecorrelation test product moment. The results of the correlation analysis of this study obtained a value of rxy= -0.452 and a significance value of p = 0.00. This means that the hypothesis is accepted the truth, namely there is a significant negative correlation between the intensity of playing online games  mobile legend with student social skills. Thus it can be concluded that, the higher the intensity of playing mobile legend online games , the lower the social skills of MAN 3 students in Banda Aceh City.Keywords : The Intensity of Playing Mobile Legend Games, Social Skills Abstrak: Intensitas bermain game online mobile legend adalah seberapa sering seseorang menggunakan waktunya untuk melakukan aktifitas bermain game online mobile legend.Sedangkan keterampilan social adalah kemampuan individu dalam berorientasi untuk mencapai tujuan ,nilai dan penerimaan dilingkungan sosialnya. Penelitian ini bertujuan untuk mengetahui hubungan antara intensitas bermain game Mobile Legend dengan keterampilan sosial siswa. Penelitian ini dilakukan dengan pendekatan kuantitatif deskriptif serta menggunakan teknik observasi skala. Subjek penelitian ini dipilih menggunakan purposive sampling, yaitu pengambilan sampel berdasarkan ciri-ciri atau sifat-sifat tertentu. Subjek dari penelitian ini adalah siswa MAN 3 Kota Banda Aceh yang bermain game mobile legend. Hasil penelitian menunjukkan bahwa intensitas bermain game online mobile legend  pada siswa MAN 3 Kota Banda Aceh berada pada kategori, sementara kualitas keterampilan sosial siswa juga berada pada kategori sedang. Adapun teknik analisis data yang digunakan dalam spenelitian ini untuk menjawab rumusan masalah 1 dan 2 adalah analisi deskriptif persentase, sedangkan untuk rumusan masalah nomor 3 menggunakan uji korelasi product moment. Hasil analisis korelasi penelitian ini didapatkan nilai rxy= -0,452 dan nilai signifikasi p=0,00. Artinya Hipotesis diterima kebenarannya, yaitu terdapat korelasi negatif yang signifikan antara Intensitas bermain game online mobile legend dengan keterampilan sosial siswa. Dengan demikian dapat disimpulkan bahwa, semakin tinggi intensitas bermain game online mobile legend maka akan semakin rendah keterampilan sosial siswa MAN 3 Kota Banda Aceh. Kata Kunci : Intensitas Bermain Game Mobile Legend, Keterampilan Sosial